2013
DOI: 10.1007/s11999-012-2556-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Fresh Osteochondral Allografts Successfully Treat Femoral Condyle Lesions?

Abstract: Followup of femoral condyle osteochondral allografting demonstrated durable improvement in pain and function, with graft survivorship of 82% at 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
226
2
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(248 citation statements)
references
References 34 publications
7
226
2
13
Order By: Relevance
“…10 Other studies have highlighted that patients older than 30 years at the time of surgery and with 2 or more prior surgeries were more likely to have allograft failure. 11 These studies demonstrate that patient selection and injury timing are crucial for both patient selection and the survival of large osteochondral allograft transplants.…”
Section: Discussionmentioning
confidence: 89%
“…10 Other studies have highlighted that patients older than 30 years at the time of surgery and with 2 or more prior surgeries were more likely to have allograft failure. 11 These studies demonstrate that patient selection and injury timing are crucial for both patient selection and the survival of large osteochondral allograft transplants.…”
Section: Discussionmentioning
confidence: 89%
“…6,[8][9][10] A retrospective study of 46 patients by Gracitelli et al 8 reported an 87.4% 10-year graft survivorship. A prospective study of 25 patients by McCulloch et al 9 reported graft incorporation into host bone in 22 of 25 (88%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…LaPrade et al 6 followed 23 patients over 3 years and showed improvement in Cincinnati scores from 49.2 to 69.0 (P < .02), International Knee Documentation Committee score improvement from 52.0 to 68.3 (P < .03), and evidence of graft healing in 22 of 23 patients (96%). Recently, Levy et al 10 reported a retrospective case series of 122 patients (129 knees) between 1983 and 2011, with a survivorship of 82% at 10 years, 74% at 15 years, and 66% at 20 years. However, the applicability of this study is limited as a result of their allografts being transplanted within 7 days postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of using exogenous biomaterials, scaffold-free • Short-term clinical results not sustained through long-term followup [16][17][18]24,27,95] Osteochondral autograft (mosaicplasty)…”
Section: Drawbacks Of Current Tissue Engineering Approaches For Osteomentioning
confidence: 99%